PROSES BIMBINGAN BELAJAR PADA LEMBAGA BIMBEL GANESHA OPERATION KELURAHAN SIDOMULYO KECAMATAN TAMPAN KOTA PEKANBARU - Esra Vebriani Br. Situmeang; Said Suhil Achmad; Titi Maemunaty (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study examines the Guidance Process at the Ganesha Operation Bimbel Institute, Sidomulyo Village, Tampan District, Pekanbaru City, and in the process there are showing, guiding, guiding, assisting in the Tutoring Process. The purpose of this study was to find out and analyze how the process of tutoring at the Ganesha Operation Bimbel Institute, Sidomulyo Village, Tampan District, Pekanbaru City. This type of research is descriptive with a qualitative approach, in which the data collection process is carried out by interviewing 4 subjects, namely control informants, core informants 1, core informants 2, core informants 3 with documentation included. Based on the results of interviews, researchers found 4 indicators, namely: (1) Showing, (2) Guiding, (3) Guiding, (4) Helping. The study of the 4 indicators is very useful for understanding how the stages of the process of implementing teaching and learning activities are appropriate in conducting the tutoring process.Key Words: Guidance, Study, Ganesha Operation